1995
DOI: 10.1163/156939395x00613
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a wire antenna of arbitrary shape

Abstract: A fast yet accurate method for analyzing a wire antenna of arbitrary shape is developed. In addition to the straight line in a wire grid model, a new canonical element, namely, an arc of constant radius of curvature is introduced. For a curvilinear antenna, combination of bent and unbent lines could substantially reduce the fitting error. A technique is devised that solves the vector wave equation on the surface of an arced segment as simple as if it were a straight one. As each segment is relatively long in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 6 publications
2
0
0
Order By: Relevance
“…The simulations for small wire radius was in advance made for verification of the program code in Fortran. The numerical results from this paper and the literature [14], [15] are plotted in Fig. 3(b) and it can be found that our results are in good agreement with those in [14], [15].…”
Section: Numerical Results and Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The simulations for small wire radius was in advance made for verification of the program code in Fortran. The numerical results from this paper and the literature [14], [15] are plotted in Fig. 3(b) and it can be found that our results are in good agreement with those in [14], [15].…”
Section: Numerical Results and Discussionsupporting
confidence: 82%
“…The numerical results from this paper and the literature [14], [15] are plotted in Fig. 3(b) and it can be found that our results are in good agreement with those in [14], [15]. But for a helical antenna with thick radius, the difference is obviously found while the exact kernel and thin-wire approximation are applied individually.…”
Section: Numerical Results and Discussionsupporting
confidence: 80%